AL-HAJJAJ'S INTRODUCTIONS TO POLITICAL POETRY IN THE FIRST ABBASID ERA - Bahaa Sarhan Younis , Assist. Prof. Dr. Abdulrahman Khalaf Mutlab (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
With regard to this research, I studied the common premises of the pilgrims, and the research included the arguments of the certain premises, which include facts, facts, including scientific facts, and religious facts, and dealt with common values; Including abstract values, and concrete values. The reason why I chose this topic; It is my strong desire to study the new rhetoric or what is called the rhetoric of Hajjaj; Because I found it the most appropriate in terms of interpretation and analysis of poetic texts, as well as being included in the rest of the human sciences. Its aim was to show the Arab poetic genius and its ability to form a poetic discourse that carries political and social functions. Poetry is not isolated from life, and the Arab poetic heritage has left a rational legacy that they have used since ancient times in their poetic discourse .